Structure of human resource management in the information technology field: A bibliometric analysis - Sehitoglu, Yasin; Sengullendi, Muhammet Fatih; Bilgeturk, Mahmut (URAL STATE UNIV ECONOMICS, 2022)
Human resource management (HRM) involves huge amounts of data, which requires the application of modern information technologies (IT). The paper looks at the role and development of human resource management in information technologies by employing bibliometric analysis of publications released in the period of 2001-2020 and aims to understand the interaction between the two fields. The methodological basis includes the concept of human resource management. In the article, the bibliometric methods were used, such as co-word, social network and keyword frequency analyses. The information basis of the study includes 562 articles indexed in Scopus database. The data obtained were processed using VOSviewer, Pajek and UCINET software. The 20-year period under study was divided into four periods of five years each to interpret the combination of methods, betweenness centrality and degree centrality values of the keywords for each period. Social network analysis findings reveal that sustainable HRM studies in the IT field are cohesive and connected, and appear to be building as an academic field. According to the research findings, human resource development, cloud computing, supply chain management, and job satisfaction are the most likely study fields in the future. Developments in the field of HRM provide a subjective assessment and interpretation of the emerging trends based on the quantitative approach and identify the existing research gaps, such as looking for an association between IT and sustainable HRM social effects.
Keywords: human resource management; information technology; bibliometric analysis; co-word analysis; social network; analysis; SUPPLY CHAIN MANAGEMENT; INTELLECTUAL STRUCTURE; SYSTEMS; IMPACT; EVOLUTION; PROJECT; REALM; HRM; Business & Economics